Transtympanic Facial Nerve Paralysis: A Review of the Literature. Issue 5 (May 2015) - Schaefer, Nathan; O'Donohue, Peter; French, Heath; Griffin, Aaron; Elliott, Devlin; Gochee, Peter
Abstract : Summary: Facial nerve paralysis because of penetrating trauma through the external auditory canal is extremely rare, with a paucity of published literature. The objective of this study is to review the literature on transtympanic facial nerve paralysis and increase physician awareness of this uncommon injury through discussion of its clinical presentation, management and prognosis. We also aim to improve patient outcomes in those that have sustained this type of injury by suggesting an optimal management plan. In this case report, we present the case of a 46-year-old white woman who sustained a unilateral facial nerve paresis because of a garfish penetrating her tympanic membrane and causing direct damage to the tympanic portion of her facial nerve. On follow-up after 12 months, her facial nerve function has largely returned to normal. Transtympanic facial nerve paralysis is a rare injury but can have a favorable prognosis if managed effectively.